Adsorption of Cadmium (II) Ions Using Cassava Peel Activated Carbon: Study of Adsorption Kinetics, Isotherms and Thermodynamics - Nugroho, Tri Ariyanto; Riyanto, Cucun Alep; Aminu, November Rianto (Universitas Islam Indonesia, 2024)
Heavy metals Cd2+ is a dangerous pollutant of water and ecological systems if it is above the quality standard threshold. Cassava peel has a fairly high carbon element content, namely 59,31%, so it can be used as an activated carbon to break down Cd2+ metals ions in water. This research aims to determine kinetic modeling and adsorption isotherms of Cd2+ ions using CPAC activated by H3PO4, determine the optimum pH and temperature conditions for Cd2+ ion adsorption and determine the adsorption capacity of Cd2+ ions using CPAC activated by H3PO4. CPAC is made through a carbonization process at a temperature of 500 °C for 1 hour. Next, it was impregnated with H3PO4 at a concentration of 30 % with a ratio of 1:5 (w/w) for 24 hours and physically activated at a temperature of 600 °C for 1 hour. Based on research, kinetic modeling and adsorption isotherms of Cd2+ ions using CPAC activated by H3PO4 following Pseudo-Second-Order (PSO) kinetic modeling and Freundlich isotherm, the optimum pH and temperature conditions for Cd2+ ion adsorption were obtained at pH 5 and temperature 25 °C. Thermodynamic parameters such as Gibbs energy (∆G°), enthalpy (∆H°), and entropy (∆S°), have been evaluated and indicate physical, spontaneou, and exothermic adsorption processes. The adsorption capacity of Cd2+ ions using CPAC activated by H3PO4 is 5.2219 mg/g.